Hubungan resting metabolic rate (RMR) dan komposisi tubuh dengan kadar HbA1c pada obesitas - Inggrid Lovita; Meita Hendrianingtyas; Ria Triwardhani (Intisari Sains Medis, 2019)
Background: Obesity occurs due to an imbalance intake and energy expenditure. The cause of obesity is low energy expenditure whereas the resting metabolic rate (RMR) is the largest component of energy expenditure of the body. The factors that influence RMR are body composition, age, sex and hormonal status. Body composition measured as fat mass and free fat mass (FFM). Body fat increase in obesity can cause insulin resistance which will increase blood glucose levels. This study aims to determine the correlation between RMR and body composition (fat mass and FFM) with HbA1c levels increase as a parameter of diabetes mellitus in obesity.Methods: Cross sectional study design to 38 subjects young adults obese. Resting metabolic rate and body composition (fat mass and FFM) measured with Omron Karada scan HBF 375. HbA1c measured with ion-exchange HPLC method. Statistical analysis using the Spearman’s correlation test (p<0.05)Result: HbA1c mean of 5.4% is still a normal value of HbA1c. There were no correlation between RMR and HbA1c (p = 0.768), fat mass with HbA1c (p = 0.102) and FFM with HbA1c (p = 0.843).Conclusion: RMR and body composition (fat mass and FFM) are not associated with HbA1c levels in obese young adults.